Isolation and structure determination of a new indene derivative from endophytic fungus Aspergillus flavipes Y-62. Issue 20 (18th October 2019) - Akhter, Najeeb; Pan, Chengqian; Liu, Yanqin; Shi, Yutong; Wu, Bin
Abstract: As part of the search for naturally derived secondary metabolites, a novel indene derivative, compound 1, together with nine known metabolites (2 –10 ) have been purified from an ethyl acetate extract of the plant-associated fungus Aspergillus flavipes Y-62, isolated from Suaeda glauca (Bunge) Bunge which was collected along Zhoushan coast, Zhejiang province, East China. The structure of the new compound 1 was elucidated by extensive use of spectroscopic techniques like 1D, 2D NMR, and HR-TOF-MS, while the known metabolites were established based on both spectral methods as well as by comparison with the previous literature. Compound 1 exhibited antimicrobial activities against the gram-negative pathogen Pseudomonas aeruginosa and Klebsiella pneumoniae with equal MIC values of 32 µg/ml. Abstract :